A survey on the awareness of animal cruelty towards cats and dogs in Johor Bahru, Malaysia - Bohari, Norsaadah (2015)
The awareness of animal cruelty is important for public to know treatment and management when infected by disease related with animal cruelty. This study is intended to determine the level of awareness of public on cats and dogs cruelty in Johar Bahru, Malaysia and to determine the treatment and management of diseases that related with animal cruelty. The lack of awareness may influence the knowledge of treatment and management of disease that related with animal cruelty. This study is aims to determine the level of the awareness and knowledge level of the treatment and management of disease related with cats and dogs cruelty among public. Survey was distributed to public through the use of a questionnaire. The questionnaire is consisting five different sections. The questionnaire was formulated to determine level of awareness of animal cruelty and knowledge and treatment of disease that related with animal cruelty. The level of awareness on animal cruelty towards cats and dogs among public was moderate. The knowledge level of treatment and management of disease that related with animal cruelty was low, since only four knowledge statements chosen more than 50% and the other six knowledge statements chosen less than 50% by respondents. There was moderate awareness of animal cruelty by respondents. This moderate awareness could contribute to the low knowledge on treatment and management that related with animal cruelty. It is important to educate public on animal cruelty in pets especially cats and dogs. This is to encourage them to practice proper treatment and management.